2018
DOI: 10.1007/s11128-018-1960-4
|View full text |Cite
|
Sign up to set email alerts
|

Using three-partite GHZ states for partial quantum error detection in entanglement-based protocols

Abstract: The problem of noise incidence on qubits taking part of bipartite entanglement-based protocols is addressed. It is shown that the use of a three-partite GHZ state and measurements instead of their EPR counterparts allows the experimenter to detect 2/3 of the times whenever one of the qubits involved in the measurement is affected by bit-flip noise through the mere observation of unexpected outcomes in the teleportation and superdense coding protocols when compared to the ideal case.It is shown that the use of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Should this not be the case, a bit-flip has occurred on one of those qubits, meaning that the teleported state can be rejected. This means that partial bit-flip errors can be detected in the teleportation protocol, [52] resulting in an improved overall fidelity [23], which is fundamental for teleportation protocols in ascertaining that the transmitted information is correct. Finally, Bob can retrieve the state in Eq.…”
Section: Ghz Channel and Measurement Teleportation Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…Should this not be the case, a bit-flip has occurred on one of those qubits, meaning that the teleported state can be rejected. This means that partial bit-flip errors can be detected in the teleportation protocol, [52] resulting in an improved overall fidelity [23], which is fundamental for teleportation protocols in ascertaining that the transmitted information is correct. Finally, Bob can retrieve the state in Eq.…”
Section: Ghz Channel and Measurement Teleportation Protocolmentioning
confidence: 99%
“…Note that the last measurement also serves to ascertain that both of the measurements on Alice's tripartite state qubits give the same measurement value, that is both ones or zeros. If they differ, then one can be certain that a bit-flip error has occurred in one of the qubits [23], allowing for the post-selection of noisy measurements, which cannot be carried out by using a Bell channel. This partial error detection leads to a better overall fidelity of teleportation.…”
Section: Localizable Concurrencementioning
confidence: 99%
See 1 more Smart Citation
“…To diversify the mathematical approach used here, let us now write the states by using the formalism of the density matrix. This problem has been discussed in [66], where was considered a maximally entangled state as the channel as well in the measurement. It was showed that this procedure can help to improve the quality of the protocol on the occurrence of bit-flip error.…”
Section: B Teleportation Of a Single Qubit State: Ghz Channel And Mementioning
confidence: 99%
“…By using the same approach, the authors of [7] contrast theoretical predictions with experimental results. In addition, there are even some approaches to the problem of multipartite noisy teleportation [8][9][10].…”
Section: Introductionmentioning
confidence: 99%